Next-generation digital payment methods - Robson, Karen (London : SAGE Publications: SAGE Business Cases Originals, 2022)
The use of next-generation digital payment methods-such as mobile payments and contactless payments-has grown rapidly during the COVID-19 pandemic. However, their full potential is far from being realized. Students are asked to discuss how the emerging generation of digital payment methods differs from the preceding generation and to assess the benefits of advanced digital payment methods. Students can also discuss potential barriers consumers have to adopting next-generation digital payment methods and can generate recommendations for financial services firms or policymakers that wish to promote adoption among consumers.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Electronic funds transfers -- Case studies; Consumer behavior -- Case studies